The Role of Parents in Supporting the Soul camp Program as an Effort to Improve Students’ Independence (Case Study at SMP IIBS Ar Rohmah Putra Malang) - Westari, Nelly (Proceedings Series of Educational Studies, 2025)
Independence is one of the crucial aspects of character development and preparing students to face future challenges. This study aims to analyze the role of parents in supporting the Soulcamp program as an effort to enhance student independence at SMP IIBS Ar Rohmah Putra Malang. The research employs a qualitative method with a case study approach. Data were collected through in-depth interviews, observations, and documentation, and analyzed using thematic analysis techniques. The research shows that parents play a main role through material, emotional support, and collaboration with the school. Parental support significantly impacts the improvement of students' independence, particularly in decision-making skills, responsibility, and managing daily tasks. However, challenges such as the lack of understanding of the program, and differences in home education patterns were identified. To address these barriers, the school builds intensive communication with parents. The Soulcamp program proves to be relevant as an Islamic character education initiative that integrates spiritual, social, and intellectual values. This study explains the importance of strong collaboration between schools and families in shaping students' character to become independen and responsible.